Population density of Indian giant squirrel Ratufa indica centralis (Ryley, 1913) in Satpura National Park, Madhya Pradesh, India - Gurjar, Raju Lal; Kumbhar, Amol .S.; Jena, Jyotirmay; Yogesh, Jaya Kumar; Dave, Chittaranjan; Singh, Ramesh Pratap; Mishra, Ashok (Journal of Research in Biology, 2013)
Information on population and distributional status of Indian giant squirrel Ratufa indica centralis is poorly known from central Indian hills. The species is endemic to India and widely distributed in Western Ghats, Eastern Ghats and Central India. In this study using line transect distance sampling we estimated population density of giant squirrel in Satpura Tiger Reserve (STR), which is a major biosphere reserve in central India that harbors wide variety of rare endemic and endangered species. Density estimate with total effort of 276km line transect shows 5.5 (± 0.82) squirrels/Km2. This study provides first baseline information on ecological density estimate of Ratufa indica centralis in central Indian landscape. Reduction of anthropogenic pressure should be the first priority for park managers in Satpura Tiger reserve.